Impact of pulmonary rehabilitation program with cycle ergometry in chronic obstructive pulmonary disease (Annals of Medical Research, 2021)
Aim: To evaluate impact of pulmonary rehabilitation (PR) on quality of life (QoL) and respiratory variables in Chronic Obstructive Pulmonary Disease (COPD).Materials and methods: PR program for 3 times per week for 8 weeks were performed in patients with COPD. Breathing, upper extremity strengthening and cycle ergometry exercises were performed. PFTs, MMRC dyspnoea scale, BODE Index and 6-minute walking test (6-MWT) were evaluated baseline and after treatment in all patients with COPD. Beck Depression Inventory and State-Trait Anxiety Inventory (STAI I and II) were used for evaluating depression and anxiety and QoL was evaluated with SF-36 scale. Patients having any other cardiac or pulmonary co-morbiditites, inability for attending rehabilitation program (due to physical, physicologic or neurologic problems) were excluded. Results: A total of 50 patients were included (45 male and 5 female patients). Mean age was 59.4±8.8 (56-62). Improvement was detected in exercise capacity, dyspnea severity, QoL, anxiety, and depression levels. Improvement in PFT results were obtained after exercise program. Conclusion: PR program with cycle ergometry is effective in patients with COPD.
Keywords: Rehabilitation; exercise; chronic lung disease; anxiety